A SINGULARIDADE DA MONTAGEM EM LEYA MIRA BRANDER (Palíndromo, 2013)
The Montage issue is dealt as an important procedure in the Leya Mira Brander’s graphic work, an artist from São Paulo. Avoiding a simple homogenization, seeks to consider the following aspects related to the Montage: by time serialization, by anachronism, by juxtaposition, by collage, by superposition, by deductive superposition and by agglomeration.
Keywords: Leya Mira Brander; metal engraving; montage procedure